2018
DOI: 10.1080/19396368.2018.1491074
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and demographic factors associated with human semen quality and sperm function

Abstract: BMI: body mass index; SA: semen analysis; AR: acrosome reaction; DFI: DNA fragmentation index; GAM: generalized additive model; TSC: total sperm count; TMC: total motile sperm count; IUI: intrauterine insemination; SCSA: sperm chromatin structure assay; SD: standard deviation; IQR: interquartile range; CBAVD: congenital bilateral absence of vas deferens; NEQAS: national external quality assessment service; HTF: human tubal fluid; HSA: human serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
5
29
0
6
Order By: Relevance
“…In the present study, a sleep duration shorter than 7.5 h was associated with reduced semen quality. Shorter sleep durations have previously been linked to reduced semen quality in a limited number of studies [8,9,13,14]. The optimal sleep duration in relation to semen quality in the most comparable study, which was conducted with Chinese university students, was 7.0-7.5 h [9] and thus shorter than in our study.…”
Section: Sleep Durationmentioning
confidence: 42%
See 4 more Smart Citations
“…In the present study, a sleep duration shorter than 7.5 h was associated with reduced semen quality. Shorter sleep durations have previously been linked to reduced semen quality in a limited number of studies [8,9,13,14]. The optimal sleep duration in relation to semen quality in the most comparable study, which was conducted with Chinese university students, was 7.0-7.5 h [9] and thus shorter than in our study.…”
Section: Sleep Durationmentioning
confidence: 42%
“…The disruption of the circadian rhythm has also been associated with lower levels of urinary 8hydroxydeoxyguanosine likely caused by reduced melatonin levels indicating a reduced ability to repair oxidative deoxyribonucleic acid (DNA) damage which is important for fertility [24]. In line with this, Shi et al [13] found a higher DNA fragmentation index (DFI) in men with irregular sleep. Prescribing regiments of reasonable bedtimes with relevant sleep durations could prove an important factor in increasing the fertility of men based on the currently available literature and the results of the present study.…”
Section: Bedtimementioning
confidence: 95%
See 3 more Smart Citations